AP205 VLPs Based on Dimerized Capsid Proteins Accommodate RBM Domain of SARS-CoV-2 and Serve as an Attractive Vaccine Candidate - Xuelan Liu; Xinyue Chang; Dominik Rothen; Mariliza Derveni; Pascal Krenger; Salony Roongta; Edward Wright; Monique Vogel; Kaspars Tars; Mona O. Mohsen; Martin F. Bachmann (Vaccines, 2021)
COVID-19 is a novel disease caused by SARS-CoV-2 which has conquered the world rapidly resulting in a pandemic that massively impacts our health, social activities, and economy. It is likely that vaccination is the only way to form “herd immunity” and restore the world to normal. Here we developed a vaccine candidate for COVID-19 based on the virus-like particle AP205 displaying the spike receptor binding motif (RBM), which is the major target of neutralizing antibodies in convalescent patients. To this end, we genetically fused the RBM domain of SARS-CoV-2 to the C terminus of AP205 of dimerized capsid proteins. The fused VLPs were expressed in E. coli, which resulted in insoluble aggregates. These aggregates were denatured in 8 M urea followed by refolding, which reconstituted VLP formation as confirmed by electron microscopy analysis. Importantly, immunized mice were able to generate high levels of IgG antibodies recognizing eukaryotically expressed receptor binding domain (RBD) as well as spike protein of SARS-CoV-2. Furthermore, induced antibodies were able to neutralize SARS-CoV-2/ABS/NL20. Additionally, this vaccine candidate has the potential to be produced at large scale for immunization programs.